Study of the dependence of the characteristics of the pulse negative corona on the parameters of the combined high voltage power supply - Taran, G.V.; Kadolin, B.B.; Ostroushko, V.M.; Paschenko, I.A. (Problems of Atomic Science and Technology, 2023)
Numerical simulations of the negative corona in oxygen-containing gases under varying voltage are carried out. It is shown that by changing the values of constant voltage and duration of its application, between high voltage pulses, it is possible to control the electric field strength near the cathode, during the pulse. Quantitative characteristics of the ozone generation process are experimentally investigated. It is found that the agreed choice of the values of the constant component of the applied voltage and the frequency of the high voltage pulses can significantly increase the productivity and energy efficiency of ozone generators. Проведене числове моделювання негативної корони у кисневмісних газах при змінній напрузі. Показано, що при зміні величини та тривалості застосування постійної напруги між імпульсами високої напруги можна керувати напруженістю електричного поля поблизу катодa під час імпульсу. Експериментально досліджено кількісні характеристики процесу вироблення озону. Виявлено, що узгодженим вибором значень постійної складової напруги живлення та частоти імпульсів високої напруги можна значно збільшити продуктивність та енергетичну ефективність генераторів озону.